2012
DOI: 10.5539/gjhs.v4n6p23
|View full text |Cite
|
Sign up to set email alerts
|

Predictors of Access to Healthcare: What Matters to Rural Appalachians?

Abstract: Objective:Lack of access to healthcare is frequently cited as a primary reason for health disparities globally, especially in poor, rural areas such as Appalachia in the U.S. This study examined predictors of perceived access to healthcare among residents in a poor, medically underserved, rural Appalachian community.Methods:The study was guided by the revised behavioral model of healthcare services utilization. Self-reported survey data were obtained from a convenience sample of 921 residents in rural Tennesse… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
10
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 14 publications
(12 citation statements)
references
References 24 publications
1
10
0
Order By: Relevance
“…According to Aday and Andersen (1998), gender is one of the predisposing factors in accessing healthcare [ 31 ]. In this study, female migrants achieved a higher accessibility to healthcare services than their male counterparts, a result that is consistent with two previous studies [ 32 , 33 ]. As in other Asian countries, males are considered as the leader of the family in Myanmar culture.…”
Section: Discussionsupporting
confidence: 93%
“…According to Aday and Andersen (1998), gender is one of the predisposing factors in accessing healthcare [ 31 ]. In this study, female migrants achieved a higher accessibility to healthcare services than their male counterparts, a result that is consistent with two previous studies [ 32 , 33 ]. As in other Asian countries, males are considered as the leader of the family in Myanmar culture.…”
Section: Discussionsupporting
confidence: 93%
“…Specifically, in the city of Detroit, being unmarried, being Black, and residing in an area of extreme poverty were all significant [ 57 ]. Health insurance is also identified as a predictor of access and use of healthcare services [ 54 , 58 60 ]. In our study, we found marital status and type of health insurance coverage played a significant role in the diagnosis of breast cancer.…”
Section: Discussionmentioning
confidence: 99%
“…Equitable access to quality health care is one of the major necessities to promoting health and well-being in minority and underserved populations, especially in poor and rural areas. 40 Evidence indicates that inequalities in health care access are primarily due to high numbers of not insured or underinsured low-income individuals. 31 , 41–45 For instance, several past studies 31 , 42–45 have found that uninsured patients and patients on Medicaid were more likely to receive a later stage BC diagnosis than women with private insurance.…”
Section: Discussionmentioning
confidence: 99%